2023
DOI: 10.2147/idr.s408976
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Intra-Host Evolution Among Drug-Resistant Tuberculosis Patients Failing Treatment

Abstract: Background Understanding Mycobacterium tuberculosis ( Mtb ) intra-host evolution of drug resistance is important for successful drug-resistant tuberculosis (DR-TB) treatment and control strategies. This study aimed to characterise the acquisition of genetic mutations and low-frequency variants associated with treatment-emergent Mtb drug resistance in longitudinally profiled clinical isolates from patients who experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Additionally, it is noteworthy that the resistance rate to fluoroquinolones is also relatively high, ranking third after rifampicin and isoniazid, although the proportion of patients with monoreistance to it is not very high. Fluoroquinolones are widely used not only for treating TB but also for other types of infectious diseases ( 22 ), which might contribute to the high fluoroquinolone resistance rate. Considering that fluoroquinolones are core drugs for treating DR-TB patients, we need to pay attention to and strengthen monitoring of its drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is noteworthy that the resistance rate to fluoroquinolones is also relatively high, ranking third after rifampicin and isoniazid, although the proportion of patients with monoreistance to it is not very high. Fluoroquinolones are widely used not only for treating TB but also for other types of infectious diseases ( 22 ), which might contribute to the high fluoroquinolone resistance rate. Considering that fluoroquinolones are core drugs for treating DR-TB patients, we need to pay attention to and strengthen monitoring of its drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Faye et al, have found the phenomenon of heteroresistance rate in the Rural Eastern Cape Province increased over time, from 9.6% in 2018 to 32.2% in 2020 ( 27 ). Recent study has characterized the trend of MTB drug resistance changes in a few TB patients during the treatment process and the proportion of drug-resistant strains indeed increases in some cases as treatment progresses, leading to complete drug resistance in later stages ( 22 ). If very low proportions of drug-resistant strains can be detected early and appropriate measures are taken to eliminate these strains, it may improve the success rate of subsequent treatment.…”
Section: Discussionmentioning
confidence: 99%